A COMPARATIVE STUDY BETWEEN LIGHT WAND AND AIRTRAQ AIDED TRACHEAL INTUBATION FOR ADULT PATIENTS WITH DIFFICULT AIRWAY UNDERGOING ELECTIVE SURGERY UNDER GENERAL ANESTHESIA - KOTA, MYTHILI; GUNTREDDY, AMAN SAI; GANESH, M VENKATA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to compare airtraq (AT) intubations and lightwand (LW) intubations in terms of safety, efficacy, ease of intubation, hemodynamic variabilities, and post-operative outcomes. Methods: A cross-sectional and randomized comparative study was conducted on sixty adult patients with a predicted difficult airway, scheduled to undergo elective surgery under general anesthesia using AT and LW intubation. Results: All the cases in both the AT group and LW group were successfully intubated, with an overall success rate of 100% in both groups. The success at the first attempt in AT group was 96.66% and that of LW group was 73.33%. Conclusion: AT had superior successful intubation conditions than LW. However, both LW and AT were proved to be safe and successful techniques of intubation in difficult airway patients.